Cannabidiol markedly alleviates skin and liver fibrosis - del Río, Carmen; Ruiz-Pino, Francisco; Prados, María E.; Fiebich, Bernd L.; Tena-Sempere, Manuel; Muñoz, Eduardo (Frontiers in Pharmacology, 2022)
Cannabidiol (CBD) has been suggested as a potential therapy for inflammatory and fibrotic diseases. CBD was demonstrated to reduce alcohol-induced liver inflammation and steatosis but its specific activity on the fibrotic process was not investigated. Herein, the antifibrotic effects of CBD in the skin were analysed in vitro using NIH-3T3 fibroblasts and human dermal fibroblasts and in vivo using the bleomycin-induced model of skin fibrosis. In a second model, non-alcoholic liver fibrosis was induced in mice by CCl4 exposure. CBD was administered daily, intraperitoneally in mice challenged with bleomycin and orally in CCl4 mice, and liver fibrosis and inflammation were assessed by immunochemistry. CBD inhibited collagen gene transcription and synthesis and prevented TGF-and IL-4 induced fibroblast migration. In the bleomycin model, CBD prevented skin fibrosis and collagen accumulation around skin blood vessels, and in the CCl4 model CBD significantly attenuated liver fibrosis measured by picrosirius red and Tenascin C staining and reduced T cell and macrophage infiltration. Altogether, our data further support the rationale of the medicinal use of this cannabinoid, as well as cannabis preparations containing it, in the management of fibrotic diseases including Systemic Sclerosis and Non-Alcoholic Fatty Liver Disease.